Interactive Multiview Video Delivery Based on IP Multicast - Jian-Guang Lou; Hua Cai; Jiang Li (Advances in Multimedia)
As a recently emerging service, multiview video provides a new viewing experience with a high degree of freedom. However, due to the huge data amounts transferred, multiview video's delivery remains a daunting challenge. In this paper, we propose a multiview video-streaming system based on IP multicast. It can support a large number of users while still maintaining a high degree of interactivity and low bandwidth consumption. Based on a careful user study, we have developed two schemes: one is for automatic delivery and the other for on-demand delivery. In automatic delivery, a server periodically multicasts special effect snapshots at a certain time interval. In on-demand delivery, the server delivers the snapshots based on distribution of user requests. We conducted extensive experiments and user-experience studies to evaluate the proposed system's performance, and found that it provides satisfying multiview video service for users on a large scale.